Peran Pendidikan Agama Islam UMSU Dalam Meningkatkan Kualitas Kelulusan Mahasiswa Prodi Pendidikan Agama Islam UMSU - Eni Miftahul Jannah; Yunda Sakinah; Hikmah Ramadhani (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
His study aims to find out and obtain information objectively about the role of UMSU Islamic religious education in improving the quality of graduation. This research uses the descriptive analysis method. The data collection technique used in this research is a literature study examining documents and conducting observations or target observations related to the topic under study. The data sources in this study were taken from Islamic religious education students who collected 29 people who were members of the WhatsApp group. Besides that, this study used data sources that come from books and journals that had relevance to the title. The results obtained from this study indicate the role of Islamic religious education at UMSU, which is felt and responded to by students of the Islamic religious education study program. From the data obtained by researchers, the role of Islamic Religious Education in improving the quality of graduates of the UMSU Islamic Education Study Program explore. Students: First, helping students to be able to know, master, and understand properly and knowledge. Second, helping to instill the principles in the students themselves while studying at UMSU. Third, provide an overview of what attitudes students should have after graduating from UMSU.